Legal Protection Of Clients Without Contract On Legal Services According To Consumer Protection Law - Islamiati M. Umar; Nirwan Junus; Melissa Towadi (Universitas Negeri Gorontalo, 2021)
This article discusses the legal protection of clients without contracts in legal services according to Law no. 8 of 1999 concerning Consumer Protection The purpose of this article is to find out the relationship between lawyers and clients in legal service agreements and to find out legal protection for clients without contracts on legal services according to Law no. 8 of 1999 concerning Consumer Protection. The method used is a normative article using library data. The result of this article is that the relationship between advocates and clients is a relationship in the form of a symbiotic mutualism that requires each other, as regulated in the Law on Advocates No. 18 of 2003 concerning Advocates that Advocates and Clients each have rights and obligations. where the advocate is obliged to provide legal assistance to the client and is entitled to an honorarium for his services. Meanwhile, the client is obliged to provide an honorarium to the advocate and is entitled to legal assistance from the advocate. while the legal protection to clients in the legal service agreement is regulated in Law no. 8 of 1999 concerning Consumer Protection, as well as the settlement method, namely through the general judiciary, the Advocate Code of Ethics Council Session, and arbitration.